Pendidikan Berkelanjutan Training First Aid dalam Manajemen Planning dan Division of Work pada Kegiatan Longmarch - Ade Chandra Kusuma; Waris Wibowo; Prasetya Sigit Santosa; Ningrum Astriawati; Iswanto Iswanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Given the magnitude of responsibility in carrying out the task of maintaining the health of the longmarch participants who traveled a distance of approximately 35 km, a clear division of work is needed, the work of First Aid in accidents team personnel. The purpose of this community service is to conduct continuous education training First Aid in management planning and division of work in the long march activity at the Yogyakarta Maritime College. The service method used is to carry out continuing education and First Aid in accident training for cadets. The result of this community service is the implementation of continuing education training First Aid for several years from 2017 until now as well as the readiness of management planning and division of work for First Aid team officers in logmarch activities at the Yogyakarta Maritime College. Overall, the results of this service not only improve the quality and competence of individual cadets, but also have a positive impact on their community and surrounding environment. Trained and knowledgeable cadets are expected to become future leaders who contribute to the development of a healthier and safer society.